ST-segment elevation myocardial infarction, systems of care. An urgent need for policies to co-ordinate care in order to decrease in-hospital mortality. (1st August 2017) - Malik, Ali Osama; Abela, Oliver; Allenback, Gayle; Devabhaktuni, Subodh; Lui, Calvin; Singh, Aditi; Diep, Jimmy; Yamashita, Takashi; Yoo, Ji Won; Malhotra, Sanjay; Ahsan, Chowdhury
Abstract: Background: Regional trends for ST-segment elevation myocardial infarction (STEMI) treatment is not known in the state of Nevada. Hypothesis: Great disparity exists for treatment for STEMI in different geographical areas of Nevada. There is a great potential to improve treatment and outcomes of STEMI patients in the State of Nevada. Methods: Admissions to non-federal hospitals in the state of Nevada, using 2011 to 2013 discharge data from the Nevada State Inpatient Data Base (acquired from Healthcare Cost and Utilization Project, Agency for Healthcare Research and Quality), were analyzed. Outpatient-onset STEMI patients were identified. The state of Nevada was divided into three divisions based on population densities, defined as population per square mile. Division A included counties with population density of < 50 per square mile, Division B included counties with population density of 50 to 200 per square mile, and Division C included counties with population density of > 200 per square mile. Trends in use of STEMI-related therapies and the impact on in-hospital mortality rates were compared. Results: Almost 20% of the patients with outpatient-onset STEMI do not get any STEMI-related therapy and have significantly higher mortality rate. Patients from Division A do not have direct access to percutaneous coronary intervention (PCI) centers. These patients receive less STEMI-related therapies. Low-volume PCI centers had equivalent mortality rates for STEMI patients who got PCI, compared to high-volume PCI centers. Conclusions: Policies must be created and processes streamlined so all STEMI patients in Nevada receive appropriate treatment.